French Women and the Age of Enlightenment - Spencer, Samia (Indiana University Press, 1992)
French Women And The Age Of Enlightenment presents a stimulating portrait of women at the most crucial and paradoxical moment in French and world history. Not until the present century have French women been as influential and prolific as they were in the Age of the Enlightenment.